Androgens predispose males to monocyte-mediated immunopathology by inducing the expression of leukocyte recruitment factor CXCL1 - Julie Sellau (Nature Portfolio, 2020)
Altered monocyte responses and testosterone levels correlate, individually, with the pathogenesis of hepatic amebiasis in mice. Here the authors show that testosterone induces enhanced TNF/CXCL1 expression and stronger proinflammatory responses in both human and mouse monocytes to support an androgen-monocyte axis of inflammation regulation.